Risk factors of acute respiratory distress syndrome in Scrub typhus - Jayasimha, Karunya; Varma, Muralidhar; Kamath, Asha; Bairy, Indira; Singh, Rahul; Mounika, Sai; Koralur, Munegowda (International Journal of Research in Medical Sciences, 2017)
Background: Scrub typhus is a common tropical infection presenting as acute febrile illness. Acute Respiratory Distress Syndrome (ARDS) is a serious complication of scrub typhus and is often associated with high mortality. This study was aimed to analyse risk factors of ARDS in Scrub typhus patients. Methods: This study was a prospective observational case control study conducted from June 2012 to June 2015 in Kasturba Hospital, Manipal, Karnataka, India. ARDS was diagnosed as per Berlin criteria. Results: During the study period, a total of 320 patients were diagnosed to have scrub typhus as per our criteria. All the patients were from state of Karnataka except for 1 patient, who was from state of Kerala. A total of 20 (6.25%) patients (cases) were diagnosed to have ARDS and 300 (93.75%) patients (controls) did not have ARDS. After multivariate analysis of the risk factors only two risk factors had significant association with development of ARDS: sepsis (OR 4.34,95% CI 0.51,36.76) and septic shock (OR 16.57 95% CI 1.64,166.76). Conclusions: ARDS is a common and serious complication of scrub typhus. It often occurs along with other complications. Presence of dyspnoea, sepsis, septic shock, hypoalbuminemia should alert clinicians about ARDS. ARDS due to scrub typhus is associated with high mortality. Early recognition and prompt therapy can reduce mortality.